The Queer Story and How to Tell It: The DSSH Model in Queer Asylum Determinations - Vanto Johanna (Retfaerd, 2022)
European and Finnish national legislation and jurisprudence leave asylum decision-makers
with a wide margin of discretion in assessing queer asylum claims. For guidance, some refugee-receiving
countries, including Finland, rely on the so-called DSSH (‘Difference, Stigma, Shame, and Harm’) model.
Analysing asylum decision-makers’ interviews qualitatively, this article explores whether the narrative of
difference embedded in the DSSH model is manifested in decision-makers’ understandings of queer asylum
determinations. This article provides unique empirical data on a credibility assessment tool that, although
endorsed and applied by a number of asylum authorities, remains understudied. The model operationalizes
abstract and affective concepts (e.g., sexual identity, stigma, shame) that are difficult even for asylum decision-makers to grasp, risking to exclude those queer asylum applicants who are unable to relate to such
culturally context-sensitive abstractions or to convey emotions. The model could reinforce asylum decision-
makers’ stereotypical, gendered notions of queer asylum applicants. It is argued that by imposing and
reproducing an essentialist narrative on queer refugees the DSSH model may function as a filtering tool
in the immigration control system.